Penguatan Idieologi dan Organisasi : Penguatan Idieologi dan Organisasi Pimpinan Daerah Muhammadiyah di Kabupaten Mukomuko - amrullah; Gunawan, Hafiz (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2024)
Muhammadiyah is an Islamic movement that implements amar ma'ruf nahi munkar. Every Muhammadiyah cadre bears responsibility in the field of da'wah, so that Muhammadiyah's vision and mission are realized optimally. Muhammadiyah is a gateway organization that provides moral and social values ​​for the benefit of the people. By carrying out activities to strengthen the ideology and organization of regional leadership of Muhammadiyah assemblies/institutions, and aum in Mukomuko district, this forms training and motivation for PDM, Majlis/lamaga, PCM, PRM, and Ortom to move. The methods used are 1) preparation stage, 2) implementation stage, and 3) evaluation stage